1999
DOI: 10.1152/ajpcell.1999.277.6.c1050
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of JAK2 and MAPK on type II nitric oxide synthase expression in skin-derived dendritic cells

Abstract: . Involvement of JAK2 and MAPK on type II nitric oxide synthase expression in skin-derived dendritic cells. Am. J. Physiol. 277 (Cell Physiol. 46): C1050-C1057, 1999.-In this report, we demonstrate that a fetal mouse skin-derived dendritic cell line produces nitric oxide (NO) in response to the endotoxin [lipopolysaccharide (LPS)] and to cytokines [tumor necrosis factor-␣ (TNF-␣) and granulocytemacrophage colony-stimulating factor (GM-CSF)]. Expression of the inducible isoform of NO synthase (iNOS) was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 38 publications
3
33
1
Order By: Relevance
“…cIrp94-treated BMDCs show a strong translocation as compared with LPS in the nucleus, which suggests the early activation of NF-B with NKR-P2 ligation. NF-B activation takes place due to the phosphorylation and degradation of IB in the cytoplasm (77); data on cIrp94-mediated degradation of I〉␣ also support the involvement of NF-〉 activation during Irp94-NKR-P2 interaction. Thus, our data suggest NF-B to be a key executioner of Irp94-mediated activation of BMDCs.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…cIrp94-treated BMDCs show a strong translocation as compared with LPS in the nucleus, which suggests the early activation of NF-B with NKR-P2 ligation. NF-B activation takes place due to the phosphorylation and degradation of IB in the cytoplasm (77); data on cIrp94-mediated degradation of I〉␣ also support the involvement of NF-〉 activation during Irp94-NKR-P2 interaction. Thus, our data suggest NF-B to be a key executioner of Irp94-mediated activation of BMDCs.…”
Section: Discussionmentioning
confidence: 67%
“…The results from the studies with pharmacological inhibitors demonstrated that NO production with Irp94-NKR-P2 interaction is regulated by PI3K, tyrosine kinase, ERK kinase, serine threonine protein phosphatase, and protein kinase C. These observations suggest the involvement of a MAPK pathway in NKR-P2-mediated DC activation. Similar pathways seem to operate in DCs for iNOS induction (77) and with Hsp60 interaction in DCs (78). However, it will be interesting to investigate the accurate signal transduction cascade upon NKR-P2 ligation with Irp94.…”
Section: Discussionmentioning
confidence: 98%
“…21 The results indicated that there was no significant toxicity of dexamethasone in the concentrations used (data not shown).…”
Section: Dexamethasone Inhibits No Production In Gm-csf-stimulated Fsmentioning
confidence: 87%
“…19,20 We have previously shown, using a mouse fetal skin dendritic cell line (FSDC) in culture, that GM-CSF, a cytokine produced by allergen-stimulated keratinocytes that promotes Langerhans cell maturation and antigen presentation, induces NO production. 21 This is dependent on the expression of iNOS and is associated with the activation of the transcription nuclear factor kappa B (NF-kB). 22 This transcription factor is present in a latent (inactive) state in the cytoplasm, bound to an inhibitor, IkappaB (IkB).…”
Section: Introductionmentioning
confidence: 99%
“…Stromal cell-derived factor (SDF)-1␣ stimulation via chemokine receptor CXCR4 led to the tyrosine phosphorylation of JAK2 in a human progenitor cell line and in human T cell lines (53, 57). JAK2 is involved in the expression of type II nitric oxide synthase (iNOS) in skin-derived dendritic cells treated with LPS (10).…”
mentioning
confidence: 99%